Synthesis of 3-ethyl-4-metyl-1h,5-dihydro-2h-pyrrol-2-one by novel palladium(ii)-catalyzed cyclization and ring-closing metathesis - Chavan, Subhash P.; Pathak, Ashok B.; Pawar, Kailash P. (Synthesis-Stuttgart, 2015)
Synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one is described starting from commercially available allylamine and 4-methoxybenzylamine employing palladium-catalyzed cyclization or ring-closing metathesis as the key steps.
Keywords: antidiabetic; cyclization; glimepiride; lactams; metabolite; pyrrolinone; Ring-closing metathesis